Drama for learning : Dorothy Heathcote's mantle of the expert approach to education - Heathcote, Dorothy, ....-; Bolton, Gavin, ....- (Heinemann : Portsmouth, 1995)
For years, Dorothy Heathcote's innovative "Mantle of the Expert" approach has benefited students and teachers all over the world. Mantle of the Expert starts with a problem or task, and, in role, teachers and students explore what knowledge they already have while making new discoveries along the way. Drama for Learning pushes the boundaries of learning, using drama to create an impetus for productive learning across the curriculum, from language arts to history, math, and science. Any one thing taught becomes meshed within broad curriculum knowledge and skills.
Keywords: Drama